Patient perceptions and expectations regarding imaging for metastatic disease in early stage breast cancer - Simos, Demetrios; Hutton, Brian; Graham, Ian D; Arnaout, Angel; Caudrelier, Jean-Michel; Mazzarello, Sasha; Clemons, Mark (Université d'Ottawa | University of Ottawa, 2014)
Abstract Purpose The probability of detecting radiologically evident metastatic disease in asymptomatic women with newly diagnosed operable breast cancer is low. Despite the recommendations of most practice guidelines imaging is still frequently performed. Relatively little is known about what patients believe is important when it comes to radiologic staging. Methods Patients with early stage breast cancer who had completed their definitive breast surgery were surveyed about their personal experiences, perceptions, and expectations on the issue of perioperative imaging for distant metastatic disease. Results Over a 3 month period, 245 women with primary operable breast cancer completed the questionnaire (87.0% response rate) and 80.8% indicated having had at least one imaging test for distant metastatic disease. These were either of the thorax (72.2%), abdomen (55.9%) or skeleton (65.3%) with a total of 701 imaging tests (average of 3.5 tests per patient imaged) performed. Overall, 57.1% indicated that they would want imaging done if the chance of detecting metastases was ≤10%. Although 80.0% of patients indicated that, “doing whatever their doctor recommended” was important to them, 70.4% also noted that they would be uncomfortable if their physician did not order imaging, even if this was in keeping with practice guidelines. Conclusions Most patients with early stage breast cancer recall having imaging tests for distant metastases. Given the choice, most would prefer having imaging performed, even if this is not in line with current guidelines. If patient expectations are, in part, driving excessive imaging, new strategies addressing this are required.